Irish public service broadcasting: a contingent valuation analysis - Delaney, Liam; O'Toole, Francis (Economic & Social Studies, 2004)
Irish public service broadcasting faces enhanced domestic and international competition and increasingly the Irish public service broadcaster (RTE) is being called upon to justify the scale of the television licence fee, its major source of funding. This paper describes the first nationwide valuation of RTE?s services. In analysing the determinants of respondents? willingness to pay for RTE?s services, the importance of domestic and international competing services and the relationships between willingness to pay for, usage of, and satisfaction with, RTE?s services are analysed. In addition, this paper highlights the importance of distinguishing between household, and individual, willingness to pay.
Keywords: Public service broadcasting; Contingent valuation; Ireland; RTE